Effect of Fear on Interacting Species Dynamics with Nonlinear Predator Harvesting - Guin, Lakshmi Narayan; Mapa, Ayantika; Chakravarty, Santabrata (Journal of Environmental Accounting and Management, 2026)
The present pursuit concerns itself with an updated real predator-prey system based on a fear factor induced by interacting species with nonlinear predator harvesting unlike constant or linear harvesting. The diversification of system parameters gives rise to different categories of system dynamics. The system under consideration does experience bifurcation (saddle-node, transcritical and Hopf-Andronov) about the co-existence equilibrium position with respect to the choice of fear factor or nonlinear harvesting factor as a parameter of significance. The direction of the Hopf bifurcation together with the stability of the bifurcating periodic solutions are perceived through an explicit algorithm duly established by making use of the normal form and central manifold theory. The findings of the present investigation reveal that the fear factor or nonlinear harvesting factor bears the potential to influence the dynamical scenario of the interacting species remarkably.